The AMA handbook of project management - Dinsmore, Paul C.; Cabanis-Brewin, Jeannette (AMACOM, 2014)
The fourth edition of The AMA Handbook of Project Management provides readers with a clear overview of a complex discipline. An essential reference to the critical concepts and theories all project managers must master, the book addresses project initiation and planning; communications and interpersonal skills; scheduling, budgeting and meeting business objectives; managing political and resource issues; implementing a project management office; measuring value and competencies; and much more. Compiling essays and advice from the field's top professionals, this updated edition covers everything.